2D Structured Nano‐Sheets of Octadecylamine Grafted Graphitic‐Carbon Nitride (g‐C3N4) as Lubricant Additives. Issue 1 (18th December 2017) - Kumar, Ajay; Thakre, Gananath D.; Arya, Pankaj K.; Jain, Amar K.
Abstract : The present paper introduces new type of 2D structured nano‐sheets as additives for lubricating oils. The 2D structured nano‐sheets of graphitic‐C3 N4 (g‐C3 N4 ) have been grafted with Octadecylamine to be used as additives. The nano‐fluids have been synthesized by blending amine grafted g‐C3 N4 in lubricating oil in different weight percentage. A stable dispersion of g‐C3 N4 in the base fluids has been achieved. The dispersion stability of nano‐fluids has been studied using UV‐visible spectrometer. The grafted g‐C3 N4 nano‐sheets were characterized by analytical techniques like FT‐IR, TGA, TEM and EDX. The tribological properties of grafted g‐C3 N4 nano‐fluids have been evaluated using 4 ball tribo‐tester using standard ASTM D: 4172B procedure. The comparative assessment of tribo‐performance reveals that amine grafted g‐C3 N4 nano‐fluid significantly improve the anti‐friction and anti‐wear property. For a given concentration the g‐C3 N4 nano‐fluids reduces friction and wear by 32 % and 17 % respectively as compared base fluid.